Communication and computation rate-cheating problems in divisible load scheduling: revisited - Ghanbari, Shamsollah; Othman, Mohamed; Sembiyev, Ordabay; Umarova, Zhanat (2015)
There is extensive literature concerning the Divisible Load Scheduling (DLS). It is a paradigm in the area of parallel and distributed computing. Based on the DLS the computation and communication can be divided into some arbitrary independent parts, in which each part can be processed independently by a processor. The traditional divisible load scheduling assumes that the processors report their true computation and communication rates. In the real applications, the processors may cheat the algorithm which means that the processors might not report their true computation or communication rates. However, the computation rate-cheating problem has been investigated in several research. According to the researchers, the divisible load scheduling only obtains its optimal performance if the processors report their true computation rates. This paper revisits the research concerning the communication and computation rate-cheating problems focusing the effects and open problems.